Corpus Alienum Nasal Sinistra : Case Report - Rachel Ratu; Muhammad Fajar Ramadhan Isryal (Eduvest - Journal of Universal Studies, 2025)
Foreign bodies are one of the emergency cases in ENT where 19% of cases are located in the nose, which mostly occurs in children under five years. There are two types of foreign bodies, namely exogenous and endogenous. There are factors that can make it easier for foreign body aspiration such as personal factors, failure of normal protective mechanism, physical factors, incomplete swallowing, psychological factors and the nature of the foreign body. The process of removing foreign objects in the nose requires adequate lighting, caregiver if the patient is less cooperative, the use of cotton tampons, suction, bayonet forceps, alligator forceps and if available a nasal endoscope that is better at imaging and magnifying to identyfing the exact pathological condition.